Factors Affecting Dividend Policy: An Evidence from Indonesian Financial Companies - Cacik Rut Damayanti; Yalissa Adella Palinggi (Universitas Negeri Semarang, 2023)
The main purpose of this research is to examine how dividend policy is influenced by Corporate Governance, Profitability, and Tobin's Q Ratio. The study used proxies such as Board of Directors, Proportion of Independent Commissioners, and Institutional Ownership as proxy for Corporate Governance. To assess the profitability, this study use Return of Assets and Return of Equity. Besides, the other indicator is Tobin's Q Ratio. The research population was 94 companies from financial sector and a sample of 20 companies with 100 units of data analysis. The data for the study were analysed by using multiple linear regression analysis, using IBM SPSS Statistics. The results of this study indicate that simultaneously Corporate Governance, Profitability, and Tobin's Q Ratio have a significant effect on the Dividend Pay Out Ratio. While the Board of Directors, the Proportion of Independent Commissioners, and Return on Asset have negative significant affect the Dividend Pay Out Ratio. Meanwhile, Institutional Ownership, Return on Equity and Tobin’s Q Ratio show a positive and significant direction towards the Dividend Pay Out Ratio. This research's results can be a recommendation as one of the primary considerations, either the supporting references in making decisions before investing in the company, especially in financial listed companies.